2021
DOI: 10.1021/acsanm.1c02090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Oxide on the Pore Structure of Cement Paste: Implications for Performance Enhancement

Abstract: The effect of graphene oxide (GO) nanosheets on the spatial distribution of cement paste pores has been investigated. In this study, a scheme based on the radial distribution function is developed to analyze the spatial distribution of pores in GO−cement composites. By applying the developed scheme, the addition of 0.04% GO is found to reduce the spatial inhomogeneity of pores in cement paste by around 20% at all curing ages. The test results show that the compressive strength of the cement paste sample contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Therefore, they can act as nucleation points in the cementitious environment, accelerating the hydration process and strengthening the nanostructure in the hardened state. In addition, the nanometer size of particles can favor changes in rheological behavior, reduce porosity, improve mechanical performance, and increase durability. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they can act as nucleation points in the cementitious environment, accelerating the hydration process and strengthening the nanostructure in the hardened state. In addition, the nanometer size of particles can favor changes in rheological behavior, reduce porosity, improve mechanical performance, and increase durability. , …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the nanometer size of particles can favor changes in rheological behavior, reduce porosity, improve mechanical performance, and increase durability. 5,6 The emerging structural properties of layered double hydroxides (LDH) make them potential candidates for applications as smart functional additives in hydrated cement, producing high-performance materials. 7−10 The LDH structure consists of stacked layers formed by hydroxyl octahedra with embedded divalent (M 2+ ) and trivalent (M 3+ ) metal cations, r e p r e s e n 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…When the age was 28 d, with the increase of GO content, the small capillary pore volume increased by approximately 6.2–18.8%, while the gel pore volume only increased by approximately 1–8.9%, they demonstrated that the optimization effect of GO on the pore structure of cement paste decreases with age, as shown in Figure . Ruan et al studied the regulation of GO on the pore structure of cement paste in the range of 0.1–30 μm using metal intrusion technology and obtained similar conclusions. They observed that when the age was 7 d, the maximum pore size of the cement paste reduced from 27 to 19 μm with 0.04% GO, and the critical pore size had no significant change.…”
Section: Dispersive Properties Of Gomentioning
confidence: 79%
“…Conventional concrete has been a great limitation to the modernization of the construction industry, over the past few decades, due to its low tensile strength, quasi-brittle structure, and vulnerability to chemical attacks. Nanotechnology appears to be a promising way to revolutionize concrete manufacturing, and study in this field can bring significant performance rewards for the construction industry. A review of the literature shows that nanoparticles such as nanosilica, carbon nanotube (CNT), and graphene oxide (GO) can improve microstructure, ,, enhance mechanical properties, and provide better electrical and thermal properties of cementitious composites. …”
Section: Introductionmentioning
confidence: 99%